2018
DOI: 10.1111/nep.13471
|View full text |Cite
|
Sign up to set email alerts
|

How to treat patients with chronic kidney disease: With special focus on IgA nephropathy

Abstract: Chronic kidney disease has become a worldwide problem. Among chronic kidney disease patients, IgA nephropathy is common in the world. Serum levels of galactose deficient (Gd)‐IgA1 and Gd‐IgA1‐specific antibodies are elevated in most IgA nephropathy patients. Glomerular Gd‐IgA1 deposition has been observed by immunofluorescence. There are many reports that the anti‐proteinuric effect is significantly greater in groups who receive tonsillectomy with steroid pulse therapy in IgA nephropathy patients. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Tomino found that glomerular disease and metabolic disease can cause different degrees of infection in CGD patients, which were caused by primary glomerular disease (such as glomerular minimal disease, focal segmental glomerulosclerosis, membranous nephropathy, and proliferative glomerulonephritis), glomerular disease caused by systemic diseases (such as lupus nephritis, allergic purpura nephritis, and systemic infections), and vascular disease (Tomino, 2018). In addition, Floege suggested that glomerular disease can be caused by drug damage and infection, especially acute glomerulonephritis and cross‐immunity caused by infections from the respiratory tract, leading to kidney damage (Wang & Fey, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomino found that glomerular disease and metabolic disease can cause different degrees of infection in CGD patients, which were caused by primary glomerular disease (such as glomerular minimal disease, focal segmental glomerulosclerosis, membranous nephropathy, and proliferative glomerulonephritis), glomerular disease caused by systemic diseases (such as lupus nephritis, allergic purpura nephritis, and systemic infections), and vascular disease (Tomino, 2018). In addition, Floege suggested that glomerular disease can be caused by drug damage and infection, especially acute glomerulonephritis and cross‐immunity caused by infections from the respiratory tract, leading to kidney damage (Wang & Fey, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(A: the patient's age and course of disease; B: the patient's systolic and diastolic blood pressure) F I G U R E 6 Patient's infection types. (A: a, b, c, d, and e indicated lupus nephritis, primary nephritis, immunoglobulin nephropathy, mesangial proliferative glomerulonephritis, and minimal changes, respectively; B: a, b, c, d, and e indicated diabetic nephropathy, rapidly progressive glomerulonephritis, glomerulosclerosis, purpuric nephritis, membranous proliferative glomerulonephritis, respectively)glomerulonephritis), glomerular disease caused by systemic diseases (such as lupus nephritis, allergic purpura nephritis, and systemic infections), and vascular disease(Tomino, 2018). In addition, Floege suggested that glomerular disease can be caused by drug damage and infection, especially acute glomerulonephritis and cross-immunity caused by infections from the respiratory tract, leading to kidney damage(Wang & Fey, 2018).In this study, patients with CGD were diagnosed with symptoms and signs observation diagnosis, combined diagnosis of blood test and urine test, and health information data diagnosis based on CNN deep learning, respectively, to study the infection factors in CGD patients based on diagnosis by health information data of deep learning.…”
mentioning
confidence: 99%
“…In a discussion on periodontal therapy in patients with CKD, we must also take into consideration the influence of immunosuppressive agents. In short, a variety of CKD, such as lupus nephritis and IgA nephropathy, is commonly treated with immunosuppressive agents [76,77]. Undoubtedly, the immune response is closely associated with infection control in almost organs and tissues including oral and periodontal tissues.…”
Section: Periodontal Disease and Chronic Kidney Diseasementioning
confidence: 99%
“…Secondary adrenal insufficiency (AI) due to long-term glucocorticoid medication in patients on hemodialysis (HD) is a diagnostic challenge, as many kidney diseases are treated with corticosteroids, and immunosuppressive therapy after renal transplantation often includes prednisolone [1][2][3][4][5][6]. This is further complicated, as AI and renal replacement treatment may both lead to the same unspecific symptoms like fatigue and orthostatic hypotonia [1,3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%